A New Culture Embracing Sustainability for Apparel and Textiles Educational Programs - Grit Vece (Adult Education Research Conference, 2015)
This paper examines an interdisciplinary body of literature to highlight social change theory and its significance to apparel and textiles educational programs in promoting change in behavior towards a sustainable future. This research concludes consumer education is needed and that education can create social change.
Keywords: social change; consumer education; apparel and textiles; behavior change; sustainability education